Association between cognitive impairment and guideline adherence for application of chemotherapy in older patients with breast cancer: Results from the prospective multicenter BRENDA II study. Issue 3 (3rd April 2019) - Leinert, Elena; Schwentner, Lukas; Blettner, Maria; Wöckel, Achim; Felberbaum, Ricardo; Flock, Felix; Kühn, Thorsten; Denkinger, Michael Dieter; Janni, Wolfgang; Kreienberg, Rolf; Singer, Susanne; ,
Abstract: Background: This study examined the association between cognitive impairment and guideline adherence for application of chemotherapy in older patients with breast cancer. Patients and methods: In the prospective multicenter cohort study BRENDA II, patients aged ≥65 years with primary breast cancer were sampled over a period of 4 years (2009‐2012). A multiprofessional team (tumor board) discussed recommendation for adjuvant chemotherapy according to the German S3 guideline. Cognitive impairment was screened by the clock‐drawing test (CDT) prior to adjuvant treatment. Results: Two hundred and sixty‐three patients were included in the study and CDT data were available for 193 patients. Thirty‐one percent of the patients had cognitive impairment with different degree of severity. In high‐risk patients (n = 61) tumor board recommendation in favor of chemotherapy was 90% and in intermediate‐risk patients (n = 170) 27%. Not receiving recommendation for chemotherapy in spite of guideline recommendation was more frequent in patients with cognitive impairment (67%) vs patients without cognitive impairment (46%) with P  = 0.02 (OR 2.4, 95% confidence interval (CI) 1.2‐4.9). Age, education, migration background and comorbidities were not associated with chemotherapy recommendation by the tumor board among cognitively impaired patients. Once the tumor board had recommended chemotherapy, application of chemotherapy was similar in both groups of patients with or without cognitive impairment. Conclusion: Almost one third of older patients with breast cancer are affected by cognitive impairment prior to adjuvant treatment. In these patients, cognitive impairment was associated with tumor board decision against chemotherapy in spite of a positive guideline recommendation.